Persistent Handwriting Difficulties in Children With ADHD After Treatment With Stimulant Medication. (July 2015) - Brossard-Racine, Marie; Shevell, Michael; Snider, Laurie; Bélanger, Stacey Ageranioti; Julien, Marilyse; Majnemer, Annette
Objective: Children with ADHD often present with handwriting difficulties. However, the extent to which motor and attention skills influence performance in this group has not yet been explored. The objective of this study was to examine the factors associated with change in handwriting performance.Method: This study examines the factors associated with change in handwriting performance of 49 children newly diagnosed with ADHD (mean age = 8.4 [SD=1.3] years) prior to and 3 months following use of a stimulant medication.Results: Handwriting legibility and speed improved significantly at follow-up evaluation. However, most of the children with legibility difficulties at baseline continued to demonstrate difficulties when evaluated 3 months after initiation of medication. Change in handwriting legibility was best determined by improvements in visual-motor integration skills (β = 0.07-0.10; p < .001), while the change in speed did not appear to be consistently related to a single factor.Conclusion: Handwriting difficulties are common in children with ADHD, and medication alone is not sufficient to resolve these challenges.